Model Penanganan Sampah Berbasis Nilai Gotong Royong (Studi di Desa Sigerongan, Lombok Barat) - Hayati, Komala Mala; Sumardi, Lalu; Alqadri, Bagdawansyah; Kurniawansyah, Edy (Journal of Civic Education, 2024)
Waste management is essential for maintaining environmental cleanliness and reducing the adverse effects of waste on community well-being. In Sigerongan Village, particularly in Dusun Berembeng Barat, a community-based waste management strategy is doing based on mutual cooperation (gotong royong. This article aims to explore the application of mutual cooperation in waste management and to identify factors that support and hinder the program’s implementation. Using a qualitative approach and a case study method, data were collected through observation, interviews, and documentation. The findings indicate that waste management in Dusun Berembeng Barat is characterized by active community involvement, especially in waste collection and handling activities. The program’s success is bolstered by the participation of village authorities, community enthusiasm, and a shared commitment to environmental cleanliness. Nevertheless, challenges persist, such as limited funding and insufficient infrastructure. This community-driven approach to waste management has positively impacted the community, notably by enhancing environmental awareness and strengthening communal bonds. Continued support from both government and community members is anticipated to sustain the program’s success.